Environmental engineering with an occupational safety and health perspective - Salman, Meriç Yilmaz (Nova Science Publishers, Inc., 2023)
98% of work accidents are caused by human errors and factors arising from the workplace environment. In other words, the prevention of occupational accidents and occupational diseases, except for 2%, depends on the full implementation of occupational health and safety rules. The complete implementation of these rules depends on the laws within the scope of occupational health and safety and the awareness of the dangers and risks that the employees will encounter. However, knowing the sector very well and having a good command of the work we do enables us to be prepared for the dangers and risks arising from the nature of the work. Environmental engineering has a very comprehensive field of study. Since the sectors related to environmental engineering are different and diverse, occupational health and safety measures for people working in the sector should be evaluated separately. In this section, wastewater treatment plants and hazardous waste facilities, which are the main fields of activity of environmental engineering, will be discussed under separate headings in terms of occupational health and safety. Occupational health and safety measures to be taken against the dangers and risks that may be encountered in each field of activity will be examined. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: Hazardous waste facilities literature review; Mobile technologies; Occupational safety and health; Smart phones; Wastewater treatment plants